Criminal victimization of the deaf - Barrow, Lauren M. (Criminal justice recent scholarship, 2008)
Society's elements and the deaf -- Experience -- Peeling back the layers of social discrimination -- Deaf persons as victims -- Research methodology and data -- The data and what it reveals -- Research contributions